Adult learning in the milieu of a local environmental movement - Giannakopoulou, Eleni (Adult Education Critical Issues, 2026)
This study investigates the processes of informal adult learning within a grassroots environmental movement in Greece. Focusing on a community collective dedicated to protecting a local creek in a northern Athens suburb, the research is grounded in the theoretical frameworks of transformative learning, communities of practice, and critical ecopedagogy. Employing a qualitative case study methodology, the analysis draws on narratives from six activists gathered through semi-structured interviews. The findings indicate that engagement in environmental activism fosters multifaceted learning, manifested through: peer knowledge exchange and experiential problem-solving; identity transformation and civic empowerment; the development of embodied and affective ecological awareness; and the emergence of grassroots pedagogies for mentoring and public engagement. Conversely, participants also cited significant challenges, including activist burnout, institutional neglect, and a lack of formal recognition for their knowledge. In conclusion, this study demonstrates that environmental movements serve as dynamic learning ecosystems where adults cultivate critical, relational, and embodied knowledge.